SEMANTIC ANALYSIS ON LEXICAL RELATIONS IN PUJAKESUMA LANGUAGE - Rafida, Tien (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
Human beings need language as their communication because language as the branch of linguistic. When all people speak in a communication is a process and then, there must be both sender and receiver. Sometimes, all people only talk interaction not only directly interact and something more meaningless. In the branch of linguistics, semantic is the study about all the aspects of meaning outside the grammatical of language which different with morphology and syntax that concern with grammatical of language. In this paper, the writer interest to discuss about semantic analysis on lexical in Pujakesuma because semantics is one of the important aspect in linguistics and lexical of Javanese society nomads in Sumatera Utara (Pujakesuma) is also have different meaning to be analyzed.